Political costs, monitoring mechanisms, and tax avoidance: case of the hospitality industry / Alwan Sri Kustono, Rochman Effendi and Anindya Dianing Pratiwi - Sri Kustono, Alwan; Effendi, Rochman; Pratiwi, Anindya Dianing (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study aimed to examine the causes of tax avoidance in the hospitality sub-sectors based on political costs and monitoring mechanisms. Data were collected from the Indonesia Stock Exchange for the 2014-2021 reporting period, resulting in 168 firm-year observations. Nine hypotheses were tested using variant-based SEM with Partial Least Square. The results showed that political costs, monitoring mechanisms, financing decisions, and financial distress influenced tax avoidance choices in stable conditions. Different results were found during the pandemic, only political costs and financial distress affected tax avoidance. These findings could help stakeholders in decision-making by understanding the indicators of their tendencies. Mediating effects tests found no intervention function in this relationship. The implications in practice regarding the antecedents of tax avoidance in stable or unstable conditions as signals for stakeholders to assess the company's prospects in any situation. As a government, these signals can be used to create a society's interest protector.